Modelling and optimization of biomass-based cogeneration plant - Abdul Razak, N. A. A.; Abdul Halim, Abdul Razik (IOP Publishing Ltd., 2019)
High energy demand and energy availability lead to the increasing of unpleasant energy situation. It is exacerbated if fossil fuels are the only energy source as it contributes to climate change and global warming. Thus, governments are focusing on the usage of natural resources as fossil fuel substitution. This study focused on the modelling and optimization of biomass-based cogeneration plant. The objective was to model, simulate and optimize the cogeneration plant which used torrefied EFB pellet as fuel in Aspen Plus simulator. Firstly, suitable biomass resources in Malaysia was identified. Next, a typical process flow diagram of cogeneration from the published literature was referred. Then, parametric and structural optimization were conducted. From the simulation, 1.764 MW of power was generated and it was observed that pellet flow rate, water flow rate, air flow rate and boiler temperature influenced the power generated. Five options with different structural designs were formulated in GAMS. It was found that the plant should focused on producing power and medium pressure steam to optimize the profit. The findings concluded that biomass-based cogeneration plant was technically feasible to be deployed. However, further refinements in the optimization aspect should be developed to obtain a more accurate optimal results.